Analisa Risiko Kecelakaan Kerja di Departemen Logistik pada PT. Huayue Nickel Cobalt dengan Menggunakan Metode Hirarki Pengendalian Resiko dan HIRADC - Awwal Hajarul Tahir; Amri Yanuar; M. Ardhya Bisma; Abdul Tahir (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
PT. Huayue Nickel Cobalt (called hync) is a joint venture between Zhejiang Huayou Cobalt Co., Ltd. And China Molybdenum Co., Ltd. As well as Tshingshan Stainless Steel in October 2018, the business range includes resource development, a nickel-cobalt metal extraction, and an integrated to completed product processing. The project adopts third-generation High Pressure Acid Leaching (HPAL) technology, one of the most sophisticated nickel processing technologies in the world. This technology enabled the maximum use of all the components of precious metals in the laterite nickel ore. This can thus extract nickel, cobalt, and manganese both simultaneously and integrated into the production of fresh energy batteries. HIRADC plays a crucial role in the K3 management system because it serves as a cornerstone of prevention and risk control efforts. Its application helps companies in determining effective safety and occupational strategies and strategies. PT Huayue Nickel Cobalt has its own problems with implementation, and there are several obstacles, such as a lack of employee awareness of safety procedures, a standard operational breach. This problem can affect company productivity and employee welfare, so further effort is needed to improve the works surveillance and safety training systems. The application of HIRADC assists in the creation of risk-control strategies for risk-control methods is proven to be effective in providing structured guidance for risk assessment, from danger identification, risk assessment, to appropriate control recommendations. This analysis can provide a basis for management decision making.